Analisis Peraturan Bank Indonesia Nomor 11/33/PBI/2009 Terhadap Fungsi Dewan Pengawas Syariah Dalam Penerapan Good Corporate Governance - Pasaribu, Indri Lestari; Huda, Muhammad Ikhwanul; Alviani, Fitri Maulina (Universitas Cokroaminoto Yogyakarta, 2024)
This study aims to analyze the function of the Sharia Supervisory Board (DPS) in establishing Sharia financial institutions that have Good Corporate Governance in accordance with sharia principles. This type of research is normative juridical using a legal approach (statue Approch). The data sources in this study use primary and secondary data sources. Primary data sources are Bank Indonesia Regulation No. 11/33/PBI/2008 and Law No. 21 of 2008. Meanwhile, secondary data sources are various articles, books, and reports related to Islamic banking, the Sharia Supervisory Board, and sharia principles related to research. The results of the study show that the Sharia Supervisory Board has a significant role in realizing good governance in Islamic financial institutions. The function of the Sharia Supervisory Board in banking as Supervisors, Advisors, Reviewers, and Supporters in realizing good governance in Islamic financial institutions.